2009
DOI: 10.2353/ajpath.2009.080864
|View full text |Cite
|
Sign up to set email alerts
|

Positive Role of CCAAT/Enhancer-Binding Protein Homologous Protein, a Transcription Factor Involved in the Endoplasmic Reticulum Stress Response in the Development of Colitis

Abstract: Although recent reports suggest that the endoplasmic reticulum (ER) stress response is induced in association with the development of inflammatory bowel disease, its role in the pathogenesis of inflammatory bowel disease remains unclear. The CCAAT/enhancer-binding protein (C/EBP) homologous protein (CHOP) is a transcription factor that is involved in the ER stress response, especially ER stress-induced apoptosis. In this study, we found that experimental colitis was ameliorated in CHOP-null mice, suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 57 publications
4
94
1
Order By: Relevance
“…Recent evidence points to a role of CHOP in various inflammatory diseases, such as LPS-induced lung damage [10,11], chemically induced pancreatitis [13] and experimental colitis [12]. Here, we demonstrate that CHOP is indeed central in the inflammatory response of liver, fat and macrophages, as peritoneal macrophages from Chop −/− mice exhibit a blunted inflammatory response to LPS.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Recent evidence points to a role of CHOP in various inflammatory diseases, such as LPS-induced lung damage [10,11], chemically induced pancreatitis [13] and experimental colitis [12]. Here, we demonstrate that CHOP is indeed central in the inflammatory response of liver, fat and macrophages, as peritoneal macrophages from Chop −/− mice exhibit a blunted inflammatory response to LPS.…”
Section: Discussionmentioning
confidence: 65%
“…Data are shown as the means±SEM (n08). ** p<0.01 and *** p<0.001 vs WT mice stimulatory mechanisms, such as macrophage infiltration via induction of macrophage-1 antigen (MAC-1), reactive oxygen species (ROS) production via ER oxidase 1α (ERO1α) and IL-1ÎČ production via caspase-11, all resulting in mucosal cell apoptosis [12]. Finally, it has been demonstrated that CHOP is an inhibitor of the wingless-Int (WNT) signalling pathway and is necessary for normal bone development as Chop overexpression induced osteopenia [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proinflammatory effect of CHOP in beta cells may require a second signal, provided by cytokines, since CHOP induction by CPA does not amplify NF-ÎșB activation stimulated by a low concentration of IL-1ÎČ [20]. The role of CHOP in inflammatory responses (including chemokine and cytokine production) has been observed in different disease models, including myocardial inflammation [47], lung damage induced by LPS [48], inflammatory bowel disease [49] and obesity [15].…”
Section: Signal-transduction Of Upr-induced Islet Inflammationmentioning
confidence: 99%
“…In the acute model for colitis elicited by dextran sulfate sodium (DSS), increased numbers of apoptotic bodies and TUNEL-positive colonocytes have been identified, and genetic ablation of apoptotic regulators protects mice from DSS-induced colitis. 5,7,8 Therefore, inhibition of intestinal epithelial apoptosis appears to be a promising therapeutic strategy to prevent barrier disruption.…”
mentioning
confidence: 99%